Penerapan Metode Six Sigma Untuk Mengurangi Jumlah Defect Pada Proses Cetak Majalah Di Percetakan UD. Ajib Jaya - Sahid, Umar; Kalista, Anggia; Wirawan, Novi Hendra; Anggraini, Susanti Dhini (Universitas PGRI Ronggolawe, 2022)
The existence of competition among products tighter this requires every employer to provide the best for its customers. Quality assurance is one that must be met by the employer and given to the customer. Including the quality of magazine printing. Motorola Six Sigma is a method or technique of dramatic Improved quality control applied by the company Motorola, which is a new breakthrough in the field of quality management to the target 3.4 failures per million opportunities. This research was conducted at UD. Ajib Jaya, a company engaged in printing and screen printing. By using the six sigma method can be seen that the DPMO (defects per million opportunities) of disability and magazine print production process sigma achievement that has not been consistent, ie 3368.12 4.21 DPMO and sigma capability. Implementation of six sigma quality improvement on this study it can be concluded that there are three types of defects with the most potential are: mold mbleber 42,5%, 33,7% and double writing paper folded 18,7%